A Proposed Method to Solve Quadratic Fractional Programming Problem by Converting to Double Linear Programming - Majeed, Amir Sabir; Abed, Fadhil Salman (Sulaimani Journal for Pure and Applied Sciences, 2017)
Quadratic fractional program is an optimization problem which solving the problem by minimizes or maximizes a quadratic fractional objective function subject to finite number of linear inequality (equality constraints) . In our paper, we proposed a new method to solve quadratic fractional programming problem (QFPP),the objective function of quadratic optimization has linear factorized as product of two linear functions, the two positive linear functions solved separately by using simplex method. These are useful in solving the problem in multi-application, like economics, hospital and health, engineering problem, financial planning etc. In our paper, it was addressed to a variety of examples and the results were encouraging and accurate comparison with other methods with ease in the solution.
Keywords: QFPP; LP; simplex method; Optimality Conditions; quadratic programming; fractional programming; linearization